Distance education on the stakeholders\' perspectives: student\'s, instructor\'s and administrator\'s perceptions - Mantovani, Daielly Melina Nassif (2012)
Distance education (DE) in Brazilian higher education level has been growing since the early 2000. This educational method has been becoming more popular, due to its geographic and space flexibility as well as for its potential to take education to remote areas; that is, to people who would not be able to access a traditional face-to-face institution. Additionally, this growth leads to an increase in competition, which enhances the need to assess results. For this purpose there are models in the educational field that help the evaluation of programs, as well as models in the business field which use a marketing perspective and are rarely applied in educational services. Thus, this dissertation aims to evaluate DE considering students\', instructors\' and institutional (coordinators\' points of view) perceptions under a services marketing perspective. A case study was conducted considering Open University of Brazil Public Management undergraduate course. Study followed three phases. In the first phase a survey was conducted in order to acquire students\' perceptions of course quality, image, satisfaction and loyalty. In the second phase, a survey was conducted considering professors and tutors in order to acquire their attitudes toward technology and DE. Finally, in the third phase coordinators were interviewed in order to understand course\'s characteristics and their view of problems and potential strengths. Ten universities member of the Open University participated of the study, which totalizes 593 students, 120 instructors and nine coordinators. Students\' sample presented favorable perceptions of course quality, satisfaction, image, loyalty and institutional support. There is significant relationship between perceived quality and student satisfaction, as well as satisfaction and quality, directly and indirectly, influence student loyalty. Finally, image regarding the Open University influences course perceived quality. In addition, in this case there are similar proportion of men and women and male students showed slightly higher satisfaction and loyalty to the course. Instructors\' sample did not show relationship among attitudes and participation in DE nor among perceptions of technology and DE use. However, in general, instructors\' attitudes are favorable on considered dimensions. Coordinators reported within the main reasons for DE adoption the opportunity to disseminate education to unprivileged areas. In addition; some difficulties found relate to infrastructure. Gap analysis showed coordinators have higher perception scores on quality dimensions than students. In general, results for the three stakeholders were positive; considered constructs showed satisfactory results, reinforcing importance of the study of DE under business perspective in order to identify weaknesses and strengths and to conduct modifications on course strategies and policies.